Crystal Structure Prediction and Phase Stability in Highly Anharmonic Silver-Based Chalcohalide Antiperovskites - Pol Benítez; Cibrán López; Cong Liu; Ivan Caño; Josep-Lluís Tamarit; Edgardo Saucedo; Claudio Cazorla (PRX Energy)
Silver-based chalcohalide antiperovskites (CAPs), Ag_{3}BC (B=S, Se; C=Cl,Br,I), represent an emerging family of energy materials with intriguing optoelectronic, vibrational, and ionic transport properties. However, the structural features and phase stability of CAP remain poorly investigated to date, hindering their fundamental understanding and potential integration into technological applications. Here we employ theoretical first-principles methods based on density-functional theory to fill this knowledge gap. Through crystal-structure prediction techniques, ab initio molecular dynamics simulations, and quasiharmonic free-energy calculations, we unveil a series of previously overlooked energetically competitive phases and temperature-induced phase transitions for all CAP. Specifically, we identify a new cubic P2_{1}3 structure as the stable phase of all CAP containing S both at zero temperature and T≠0 K conditions. Consequently, our calculations suggest that the cubic Pm3[over ¯]m phase identified in room-temperature x-ray diffraction experiments is possibly metastable. Furthermore, for CAP containing Se, we propose different orthorhombic (Pca2_{1} and P2_{1}2_{1}2_{1}) and cubic (I2_{1}3) structures as the ground-state phases and reveal several phase transformations induced by temperature. This theoretical investigation not only identifies new candidate ground-state phases and solid-solid phase transformations for all CAP but also provides insights into potential stability issues affecting technological applications based on these highly anharmonic materials.